THE ROLE OF THE COUNTRIES OF CENTRAL ASIA AND NORTH AFRICA IN THE FORMATION OF THE NEW SILK ROAD WITHIN THE FRAMEWORK OF THE «ONE BELT AND ONE ROAD» INITIATIVE - Шокиров Т. С. (TARIXIY TADQIQOTLAR, 2025)
This article examines the role and importance of the countries of Central Asia and North Africa in the formation and development of the new Silk Road within the framework of the Belt and Road Initiative. The potential and economic opportunities of the participating countries, initiatives in creating a new model of cooperation and the basis of an economic integration platform in the future are analyzed, and the positive aspects of the “China-Central Asia-Africa” and “ChinaCentral Asia-Europe” communication formats are considered.